Pengaruh Level Ekstrak Daun Kelor Kering Dalam Pengencer Air Kelapa Muda Dan Kuning Telur Terhadap Kualitas Spermatozoa Babi Landrace - Na'u, Efraim; Kune, Petrus; Telupere, Frangky M. S. (Yayasan Sumber Daya Manusia Cerdas, 2024)
Purpose of this study was to determine the effect of dried moringa leaf extract (EDKK) in coconut water ( AKM ) and egg yolk ( KT ) diluent on the quality of semen landrace pigs. Semen was collected once a week using the massage method from 2 year old landrace male pig with normal reproductive organs. The diluted semen was stored in cold box at 18-200C and evaluated for motility, viability, abnormality and survival of spermatozoa every 8 hours. The design used was a completely randomized design consisting of six treatments and five replications so that there were 30 experimental units AKM 2.4 mL + KT 0.6 mL (P0), AKM 2.4 mL + KT 0.6 mL + EDKK 0.03 mL (P1), AKM 2.4 mL + KT 0.6 mL + EDKK 0.06 mL (P2), AKM 2.4 mL + KT 0.6 mL + EDKK 0.09 mL (P3), AKM 2.4 mL + KT 0.6 mL + EDKK 0.12mL (P4), AKM 2.4 mL + KT 0.6 mL + EDKK 0.15 mL (P5). The results showed that spermatozoa stored for 24 hours in 2.4 mL AKM diluent + 0.6 ml KT + 0.03 mL EDKK (P1) had 43% motility, 59.40% viability, 4.40 abnormality and survival 26.40 hours better (P<0.05 ) than the other five diluents, while the abnormalities and survival of spermatozoa in the five diluents were significantly different (P<0.05). The conclusion of this research is that the addition of 0.03 mL of dried moringa leaf extract to the egg yolk coconut water diluents is able to maintain the motility, viability, abnormalities survival of landrace pig spermatozoa for up to 24 hours of storage.